2006
DOI: 10.1111/j.1460-9568.2006.05120.x
|View full text |Cite
|
Sign up to set email alerts
|

Preferential responses in amygdala and insula during presentation of facial contempt and disgust

Abstract: Some authors consider contempt to be a basic emotion while others consider it a variant of disgust. The neural correlates of contempt have not so far been specifically contrasted with disgust. Using functional magnetic resonance imaging (fMRI), we investigated the neural networks involved in the processing of facial contempt and disgust in 24 healthy subjects. Facial recognition of contempt was lower than that of disgust and of neutral faces. The imaging data indicated significant activity in the amygdala and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 98 publications
(121 reference statements)
3
42
1
Order By: Relevance
“…However, it has been shown that certain basic emotions are related to very specific neural circuits. Disgust, for example, is consistently found to activate the insula across modalities (Sambataro et al, 2006). Whether part of this activation is truly supramodal could be elegantly tested with the approach presented by Peelen et al (2010).…”
Section: Review Of Peelen Et Almentioning
confidence: 98%
“…However, it has been shown that certain basic emotions are related to very specific neural circuits. Disgust, for example, is consistently found to activate the insula across modalities (Sambataro et al, 2006). Whether part of this activation is truly supramodal could be elegantly tested with the approach presented by Peelen et al (2010).…”
Section: Review Of Peelen Et Almentioning
confidence: 98%
“…Contempt was also considered as one of the basic emotions by Izard 21 . There is evidence that contempt and disgust may be mediated by different neural substrates 22 . Satisfaction is a low arousal positive emotion.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…The ability to decode emotional information communicated by facial expressions is crucial to social and interpersonal interactions (Ekman 1982) and the stimulus of happy, sad, fearful or neutral faces has been used in several neuroimaging paradigms to identify the distributed neural system associated with emotional processing: visual cortex, the cingulate, the superior temporal gyrus and the fusyform gyrus, the caudate nucleus and ventral putamen, the amygdala and the prefrontal cortex (Hennenlotter and Schroeder 2006;Ishai et al 2005;Posamentier and Abdi 2003;Surguladze et al 2005). Within this network, activation varies with the emotional expression displayed by the face, with differential responses to fear (Williams et al 2001), sadness (Schneider et al 2000), anger (Hariri et al 2000) and disgust (Sambataro et al 2006). Interestingly, many of the brain areas involved in facial affect recognition have also been implicated in the pathophysiology of mood disorders such as major depression (Davidson et al 2002(Davidson et al , 2003Drevets 2001;Fu et al 2004;Sheline et al 2001;Surguladze et al 2005) and mania (Chen et al 2006;Lennox et al 2004) and may potentially contribute to the vulnerability for negative emotion and onset of mood disorders (Leppanen 2006).…”
Section: Introductionmentioning
confidence: 96%